The Indicators of Human Well Being - Vanakornkul, Korrakot (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2019)
Well-being is a key for human resources development. In a society that the majority of people have well-being, its stability will remain and also contribute to the improvement of people. In terms of measurement, Well-Being Index is implemented as a tool to illustrate the value of well-being. In the past, Well-Being Index was identified and evaluated in a value symbolic form by itself. Later, in the consumerism society, Well-Being Index was described in a different form. Money and consuming potential of people, in terms of Gross Domestic Product and Gross National Product, were used as tools to measure the value of well-being. In the 1901s, the use of money and consuming potential as the well-being measurement tools was argued extensively. Concepts of Well-Being Index have started to change. Various dimensions are included to strengthen the Well-Being Index, for instances, social impacts, criminal problems, environmental problems, and others.